Left Main Coronary Artery Revascularization in Patients with Impaired Renal Function: Percutaneous Coronary Intervention versus Coronary Artery Bypass Grafting - Amin Daoulah; Rasha Taha Baqais; Alwaleed Aljohar; Abdulkarim Alhassoun; Ahmad S. Hersi; Wael Almahmeed; Nooraldaem Yousif; Abdulaziz Alasmari; Mohammed Alshehri; Fakhreldein Eltaieb; Badr Alzahrani; Ahmed Elmahrouk; et al. (Karger Publishers, 2023)
Introduction: The evidence about the optimal revascularization strategy in patients with left main coronary artery (LMCA) disease and impaired renal function is limited. Thus, we aimed to compare the outcomes of LMCA disease revascularization (percutaneous coronary intervention [PCI] vs. coronary artery bypass grafting [CABG]) in patients with and without impaired renal function. Methods: This retrospective cohort study included 2,138 patients recruited from 14 centers between 2015 and 2,019. We compared patients with impaired renal function who had PCI (n= 316) to those who had CABG (n = 121) and compared patients with normal renal function who had PCI (n = 906) to those who had CABG (n = 795). The study outcomes were in-hospital and follow-up major adverse cardiovascular and cerebrovascular events (MACCE). Results: Multivariable logistic regression analysis showed that the risk of in-hospital MACCE was significantly higher in CABG compared to PCI in patients with impaired renal function (odds ratio [OR]: 8.13 [95% CI: 4.19-15.76], p < 0.001) and normal renal function (OR: 2.59 [95% CI: 1.79-3.73]; p < 0.001). There were no differences in follow-up MACCE between CABG and PCI in patients with impaired renal function (HR: 1.14 [95% CI: 0.71-1.81], p = 0.585) and normal renal function (HR: 1.12 [0.90-1.39], p = 0.312). Conclusions: PCI could have an advantage over CABG in revascularization of LMCA disease in patients with impaired renal function regarding in-hospital MACCE. The follow-up MACCE was comparable between PCI and CABG in patients with impaired and normal renal function.